The Legal Position Of The Will Given To The Adopted Child As Proof Of Ownership In The Gorontalo Religious Court - Meriyani Hinelo (Universitas Negeri Gorontalo, 2019)
Abstract: The purpose of this study is to find out and analyze the Juridical Analysis of Religious Court Decision Number: 403/PDT. G/2019/PA. Gtlo Concerning the Determination of Probate Disputes and the Legal Position of the Will as proof of rights in the judgment of the Judge. Research Uses this type of normative-empirical research. Using several approaches, namely:the legal approach(statue approach), the case approach (case approach). The results of this study show that: First, that based on juridical analysis of religious court decision number: 403/PDT. G/2019/PA. Gtlo About the Determination of Will Disputes has been in line with the provisions of the event law, where the first condition that must be met by the plaintiff is regarding material conditions, while the plaintiff in his lawsuit is wrong in occupying defendant 1 and defendant 2 (two). Second, that the legal position of the Will as proof of rights in the judge's consideration is not used as a balance material by pa judges because there are defects as intended by the researcher, therefore the judge ruled the lawsuit is unacceptable(Niet Onvantkelijke Verklaard) ) which means that the case has not been completed with a positive verdict in the sense that it has not touched the subject matter and if the plaintiff wants to re-apply must complete the terms of the formil in questionKeywords: Position; Will; Dispute